Global Production Networks and Employment A Developing Country Perspective - Shepherd, Ben (OECD Publishing, 2013)
This paper provides evidence of the links between Global Value Chains (GVCs) and labour market outcomes, focusing on developing economies. The literature generally indicates that firms with international linkages-which we use here as a proxy for GVC involvement-tend to employ more workers, pay higher wages, and employ more skilled workers than firms that deal exclusively with the domestic market. Our results are consistent with existing evidence found in developed economies, with internationalised firms tending to hire more workers and pay higher wages in developing economies as well. We also find a positive significant relationship between the number of skilled workers and firms with international linkages but not in certain key economies. However, this comes more from firms who are importers, exporters and foreign affiliates rather than engaging in any of these activities individually. We attribute this finding to the predominance of assembly work performed in many of the economies under consideration, where unskilled workers tend to dominate. Finally, we see a strong, positive association between shares of female workers and firms with international linkages. Engaging in international activity is shown to provide greater opportunities for women to enter the formal labour market
Keywords: Employment; Trade